2021
DOI: 10.1002/onco.13800
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Response to HER2-Directed Therapy in Three Patients with HER2-Amplified Metastatic Carcinoma of the Biliary System: Case Study and Review of the Literature

Abstract: HER2 amplification, which results in overexpression of the receptor tyrosine kinase HER2, has been described in a wide variety of malignancies. HER2-targeting agents have been incorporated into the treatment paradigms for HER2overexpressing breast and gastric cancer. More recently, these agents have shown promise in other gastrointestinal malignancies, such as colon cancer and biliary tract tumors. Herein we discuss two patients with gallbladder carcinoma (GBC) and a third with ampullary carcinoma who were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…HER2 overexpression and gene amplifications are found most commonly in extrahepatic CCA and GBC, at a rate of 17–19% ( 32 ). Although case reports suggest that patients with HER2 overexpression respond to HER2-targeting antibodies ( 33 , 34 ), initial phase I and II clinical trials employed broad inhibitors of EGFR and HER2 (lapatinib or afatinib) and failed to demonstrate any significant benefit ( 35 - 37 ). These trials were performed in an unselected group of patients, two of which later found no evidence of HER2 overexpression in any participant.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression and gene amplifications are found most commonly in extrahepatic CCA and GBC, at a rate of 17–19% ( 32 ). Although case reports suggest that patients with HER2 overexpression respond to HER2-targeting antibodies ( 33 , 34 ), initial phase I and II clinical trials employed broad inhibitors of EGFR and HER2 (lapatinib or afatinib) and failed to demonstrate any significant benefit ( 35 - 37 ). These trials were performed in an unselected group of patients, two of which later found no evidence of HER2 overexpression in any participant.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of HER-2-directed therapy, including trastuzumab, pertuzumab, or lapatinib, suggested sustained response to these agents among nine patients with HER-2 mutated gallbladder cancer. However, despite a higher incidence of HER-2 mutations in cholangiocarcinoma compared with gallbladder cancers, five patients with HER-2 mutated cholangiocarcinoma showed no response to HER-2-directed therapy in the same study [ 36 ].…”
Section: Molecular Targetsmentioning
confidence: 99%
“… 1 , 2 The incidence of AAC is estimated to be 0.5, 0.73, and 0.96 per 100,000 persons per year in the US, Japan, and the Netherlands, respectively. 3 , 4 , 5 Despite its rarity, the occurrence of AAC has increased worldwide over the past few decades. 6 , 7 Patients with AAC tend to present typical symptoms of biliary obstruction at relatively early stages, but these symptoms are mostly non-specific and are therefore often detected incidentally during examinations.…”
Section: Introductionmentioning
confidence: 99%
“…that originates in biliary, duodenal, or pancreatic ductal epithelial cells 1,2 . The incidence of AAC is estimated to be 0.5, 0.73, and 0.96 per 100,000 persons per year in the US, Japan, and the Netherlands, respectively [3][4][5] . Despite its rarity, the occurrence of AAC has increased worldwide over the past few decades 6,7 .…”
mentioning
confidence: 99%